2008
DOI: 10.1016/j.crvi.2008.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of long-term salinity and soil drying on growth, water relations, nutrient status and proline accumulation of Sesuvium portulacastrum

Abstract: The interaction between soil drying and salinity was studied in the perennial halophyte, Sesuvium portulacastrum. Rooted cuttings were individually cultivated for three months in silty-sandy soil under two irrigation modes: 100 and 25% of field capacity (FC). The amount of the evapotranspirated water was replaced by a nutrient solution containing either 0 or 100 mM NaCl. Wholeplant growth, leaf water content, leaf water potential (Ψ w ), and Na + , K + , and proline concentrations in the tissues were measured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
77
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 41 publications
11
77
1
Order By: Relevance
“…However, the decrease of the leaf area in the presence of the water deficit was resulted in a reduction of the dry matter accumulation (Martinielli and Da Silva, 2011). Our results showed an increase of the root/shoot ratio as was mentioned by Bingcheng et al (2007) and Slama et al (2008). This indicated that water stress has entailed a severe decrease in the biomass air part than the root biomass.…”
Section: Discussionsupporting
confidence: 64%
“…However, the decrease of the leaf area in the presence of the water deficit was resulted in a reduction of the dry matter accumulation (Martinielli and Da Silva, 2011). Our results showed an increase of the root/shoot ratio as was mentioned by Bingcheng et al (2007) and Slama et al (2008). This indicated that water stress has entailed a severe decrease in the biomass air part than the root biomass.…”
Section: Discussionsupporting
confidence: 64%
“…The most negative values for leaf water potential and stem water potential have been found in plants submitted to both water stress and salinity, as both passive dehydration and salt accumulation contribute to lowering the leaf water potential [132]. According to Álvarez and Sánchez-Blanco [42,44], stem water potential measured at midday is a good indicator of stress resulting from deficit irrigation or salinity.…”
Section: Effects Of Salinity On Leaf Water Relations and Gas Exchangementioning
confidence: 99%
“…Until now, many researchers clarified numerous effects on plant growth (Ismail et al, 1994;Wang et al, 2009b), dry matter allocation (Yin et al, 2005;Mandal et al, 2006;Wu et al, 2008;Li et al, 2009;Sun et al, 2009;Gerardeaux et al, 2010), photosynthesis (Syros et al, 2004), nutrient concentration and status (Wang et al, 1998;Jose et al, 2003;Slamaa et al, 2008;Keutgen and Pawelzik, 2009). The oil palm (Elaeis guineensis Jacq.)…”
Section: Introductionmentioning
confidence: 99%